Crossing boundaries & confounding identity : Chinese women in literature, art, and film - Hughes, Cheryl D., 1945- (State University of New York Press, 2023)
"Examines literary, historical, and cultural portrayals of Chinese women, across centuries and continents"-- Provided by publisher.
Keywords: Women -- China.; Women in literature.; Women in art.; Women in motion pictures.; Femmes -- Chine.; Femmes dans la littérature.; Femmes dans l'art.; Femmes au cinéma.; SOCIAL SCIENCE / Ethnic Studies / Asian Studies.; Women; Women in art; Women in literature; Women in motion pictures; China